IMPORTANCE OF INFORMATION TECHNOLOGY IN SCIENCE TEACHING - Ochilova Dilsuz Akramovna (Лучшие интеллектуальные исследования, 2023)
Abstract: This article provides information on the role and importance of using information technologies in the educational process, the need to transition to a digital education system, and the level of use of innovative educational technologies.